PROCESS OPTIMIZATION AND EVALUATION OF QUALITY OF THE BARNYARD MILLET INCORPORATED SYNBIOTIC YOGHURT - U. A. AMRUTHA*; C. L. SHARON, P. SEEJA THOMACHAN, P. S. LAKSHMY and A. K. BEENA (The Journal of Research ANGRAU, 2023)
The study was conducted for three years (2019-2022) to optimize and evaluate the three treatments with various combinations of barnyard millet and other ingredients. Several combinations were tried, among which 50% milk and 50% barnyard millet slurry with 3% of inulin and 3% polydextrose was selected as the best with mean sores for overall acceptability of 8.72 for probiotic yoghurt, 8.85 for inulin and 8.75 forpolydextrose added synbiotic yoghurts. The viability of L. acidophilus was 11.15 log CFU/ml for probiotic, 11.16 log CFU/ml for inulin added synbiotic yoghurt and 11.17 log CFU/ml for polydextrose added probiotic yoghurt. The nutrients of synbiotic barnyard millet based yoghurt along with inulin and polydextrose added yoghurt were assessedand it was found to have major nutrients of carbohydrate 8.58 g/100 g , 8.47 g/100 g and 8.41 g/100 g, protein content of 3.52 g/100g, 3.63 g/100 g and 3.61 g/100 g, fat content of 0.63 g/100 g, 0.69 g/100 g and 0.66 g/100 g.